Analisis Pembuatan Media Pembelajaran dalam Mata Kuliah Pendidikan Multimedia oleh Mahasiswa Program Studi Teknologi Pendidikan IKIP Mataram - Wiwien Kurniawati; Muhtar Ahmad (Universitas Pendidikan Mandalika (UNDIKMA), 2018)
Abstract: The purpose of this study is to determine the extent to which the ability of higher students in makinglearning media that is feasible used in the learning process. This study used descriptive quantitative researchmethods. Data collection techniques used was observation, and questionnaires. The technique of analyzing the data was based on the feasibility criteria of the learning media, namely the aspects of coloring, aspects of the use of words and languages, aspects of the display on the screen, aspects of presentation, aspects of animation and sound. Based on the results of the feasibility test by media experts for the manufacture of learning media by students in multimedia education courses in the Education Technology study program, the percentage gain for each aspect was 57% Coloring, 55% Word and Language aspects, 58% Display aspects, Presentation aspects 57%, Animation and Sound aspects 56%, which meant the learning media made by higher students was in the Worthy category to be used in the learning process. Meanwhile, for the feasibility test of the material experts had 3 aspects, namely the aspect of Feasibility of Content, Feasibility aspect of Presentation, Contextual aspect. The results of the feasibility analysis by material experts showed that percentages for each aspect, namely the aspect of Feasibility of Content 99%, Feasibility aspect of Presentation 87%, and Contextual aspect 88%, where all aspects in the category were Very Worthy. This can be seen from the compatibility between the media made in accordance with the utilization and learning objectives. So, it can be concluded that higher students have the appropriate ability in making learning media to be used in the learning process. Abstrak: Tujuan penelitian ini yaitu untuk mengetahui sejauh mana kemampuan mahasiswa dalam pembuatan media pembelajaran yang layak digunnakan dalam proses pembelajaran. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif. Teknik pengumpulan data yang digunakan adalah observasi, dan angket. Teknik analisis data berdasarkan kriteria kelayakan media pembelajaran, yaitu aspek Pewarnaan, aspek Pemakaian Kata dan Bahasa, aspek Tampilan pada Layar, aspek Penyajian, aspek Animasi dan Suara. Berdasarkan hasil uji kelayakan oleh ahli media untuk pembuatan media pembelajaran oleh Mahasiswa pada mata kuliah pendidikan multimedia di program studi Teknologi Pendidikan, perolehan persentase untuk setiap aspek yaitu aspek Pewarnaan 57 %, aspek Pemakaian Kata dan Bahasa 55 %, aspek Tampilan pada Layar 58 %, aspek Penyajian 57 %, aspek Animasi dan Suara 56 % yang artinya media pembelajaran yang dibuat oleh Mahasiswa dalam kategori Layak untuk digunakan dalam proses pembelajaran. Sedangkan untuk uji kelayakan ahli materi memiliki 3 aspek, yaitu aspek Kelayakan Isi, aspek Kelayakan Penyajian, aspek Kontekstual. Hasil analisis kelayakan oleh ahli materi diperoleh persentase untuk masing-masing aspek yaitu, aspek Kelayakan Isi 99 %, aspek Kelayakan Penyajian 87 %, dan aspek Kontekstual 88 %, dimana semua aspek dalam kategoriSangat Layak. Hal ini dapat dilihat dari kesesuaian antara media yang dibuat sesuai dengan pemanfaatan dan tujuan pembelajaran. sehingga hal ini dapat disimpulkan bahwa Mahasiswa memiliki kemampuan yang layak dalam pembuatan media pembelajaran untuk digunakan dalam proses pembelajaran.